Functional characterization of BRCA1 gene variants by mini-gene splicing assay - Steffensen, Ane Y (Eur J Hum Genet, 2014)
Mutational screening of the breast cancer susceptibility gene BRCA1 leads to the identification of numerous pathogenic variants such as frameshift and nonsense variants, as well as large genomic rearrangements. The screening moreover identifies a large number of variants, for example, missense, silent, and intron variants, which are classified as variants of unknown clinical significance owing to the lack of causal evidence. Variants of unknown clinical significance can potentially have an impact on splicing and therefore functional examinations are warranted to classify whether these variants are pathogenic or benign. Here we validate a mini-gene splicing assay by comparing the results of 24 variants with previously published data from RT-PCR analysis on RNA from blood samples/lymphoblastoid cell lines. The analysis showed an overall concordance of 100%. In addition, we investigated 13 BRCA1 variants of unknown clinical significance or putative variants affecting splicing by in silico analysis and mini-gene splicing assay. Both the in silico analysis and mini-gene splicing assay classified six BRCA1 variants as pathogenic (c.80+1G>A, c.132C>T (p.=), c.213−1G>A, c.670+1delG, c.4185+1G>A, and c.5075−1G>C), whereas six BRCA1 variants were classified as neutral (c.-19-22_-19-21dupAT, c.302−15C>G, c.547+14delG, c.4676−20A>G, c.4987−21G>T, and c.5278−14C>G) and one BRCA1 variant remained unclassified (c.670+16G>A). In conclusion, our study emphasizes that in silico analysis and mini-gene splicing assays are important for the classification of variants, especially if no RNA is available from the patient. This knowledge is crucial for proper genetic counseling of patients and their family members.